Advancing Social Simulation: The First World Congress
DOI: 10.1007/978-4-431-73167-2_9
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Bilingualism in a Model of Language Competition

Abstract: In the general context of dynamics of social consensus, we study an agent based model for the competition between two socially equivalent languages, addressing the role of bilingualism and social structure. In a regular network, we study the formation of linguistic domains and their interaction across the boundaries. We analyse also a small world social structure, in order to capture the effect of long range social interactions. In both cases, a final scenario of dominance of one language and extinction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…The analysis of the Castelló et al (2007) model shows that neither bilingualism nor social structure is able to produce coexistence between the two equalstatus languages. Further, Castelló and co-workers concluded that bilingualism is not a stable strategy.…”
Section: Recent Modeling Approachesmentioning
confidence: 97%
See 3 more Smart Citations
“…The analysis of the Castelló et al (2007) model shows that neither bilingualism nor social structure is able to produce coexistence between the two equalstatus languages. Further, Castelló and co-workers concluded that bilingualism is not a stable strategy.…”
Section: Recent Modeling Approachesmentioning
confidence: 97%
“…The Stauffer et al (2007) simulation model was extended by Castelló et al (2007) by introducing bilingualism and social structure. Castelló's agents were allowed to speak either one of the languages A or B or to speak both, and besides d-dimensional networks, there were small-world networks, which accounted for short-and long-range interactions.…”
Section: Recent Modeling Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…En el campo de la lingüística es destacable un estudio comparativo basado en teoría de redes sociales (Castelló, 2007), en el marco de la evolución dinámica de lenguas en contacto, en un entorno de competencia lingüística. Entre los estudios políticos sobre conflictos fronterizos un buen ejemplo lo constituye (Cederman, 2003), con un análisis a nivel de superestructuras estatales sobre los agentes, mediante simulación de los cambios en las fronteras a nivel geopolítico.…”
Section: Experiencias De Simulación En Ciencias Sociales Con Smaunclassified